Reflecting on 21 years of running full PBL programs - Oliveira, José Manuel Nunes de (Frontiers in Education, 2023)
The technological programs offered at the Higher Education Polytechnic School of Águeda, one of the Departments of the University of Aveiro, have been organised, since 2001, around the Project Based Learning paradigm. This paper will briefly set the scene for the educational development and will then proceed to give an historical perspective on the curriculum developments that took place along the last twenty-one years, reflecting the experience grown on the field. Finally, the author will offer his personal perspective on the difficulties and benefits of the development and its implementation, as an engaged agent in the process. Preliminary results of a study aiming at understanding the impact of the program in its graduate’s careers will also be mentioned.